The Performance of Irregular Building Structures Using Pushover Analysis - Hanan Yurizka; Anis Rosyidah (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
High-rise buildings are at risk of collapse due to the earthquake. One method for analyzing earthquake loads is Pushover. Pushover is a non-linear static analysis to determine the behavior of a building collapse. This research was conducted to determine the performance of the setback building with a soft first story due to the earthquake based on the results of the pushover analysis curve. The structure is modeled as a 2-dimensional portal with a form of structural irregularity (setback with the soft first story) which consists of 2 structural models with different setback area ratios. The results of the analysis of this study indicate that the maximum shear force based on capacity curves in type 1 and type 2 buildings are 50260549.81 N and 53560488.63 N. Buildings with smaller setback area ratios, i.e., type 2 buildings have displacement, story drift, and base shear are more significant than type 1 buildings. Performance of type 1 and Type 2 building structures that refer to ATC-40 and FEMA 356 is at the Damage Control level.